2018
DOI: 10.7454/jpdi.v5i3.213
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Profil Keamanan Tenofovir dan Telbivudin terhadap Fungsi Ginjal pada Pasien Hepatitis B di Indonesia

Abstract: ABSTRAKPendahuluan. Tenofovir disoproksil fumarat (tenofovir) dan telbivudin merupakan dua analog nukleos(t)ida yang tersedia untuk terapi pasien hepatitis B. Tenofovir telah diketahui sebagai agen nefrotoksik pada pasien HIV, namun masih menjadi kontroversi pada pasien hepatitis B kronik. Di lain sisi, telbivudin memiliki efek proteksi terhadap fungsi ginjal dan bahkan meningkatkan estimasi laju filtrasi glomerulus (eLFG). Penelitian ini bertujuan untuk mengetahui profil keamanan terhadap fungsi ginjal dari t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…According to literature, mean age of patients with CHB ranges from 30.3 to 40.4 years [10]. Other study reported a higher mean which was 51.3 years [16]. Shi et al reported a younger range of age which was 33.7 to 35.1 years [10].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to literature, mean age of patients with CHB ranges from 30.3 to 40.4 years [10]. Other study reported a higher mean which was 51.3 years [16]. Shi et al reported a younger range of age which was 33.7 to 35.1 years [10].…”
Section: Discussionmentioning
confidence: 98%
“…Good efficacy of treatment is affected by HBeAgnegative status, lower baseline HBV DNA level, and lower HBsAg level [2], [19]. In addition, HBV virion is difficult to clear from hepatocytes because of the presence of covalently closed circular DNA in the host's cell nucleus [12], [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] One of the HBV infection transmissions, known as mother-to-child transmission (MTCT) or vertical transfer, can happen during pregnancy. 5 To stop the spread of various diseases that can be prevented by vaccination, including hepatitis B, the Indonesian government has recently included the hepatitis B vaccination for toddlers in an immunization development program known as the Expanded Program on Immunization (EPI). Vaccination efforts have been able to reduce the number of people with the HBB and acute morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO, after completing the recommended immunization schedule, Hepatitis B vaccination should result in a level of antibody protection in 95% of individuals. [3][4][5] Several related studies have shown that titers of Hepatitis B surface antibodies (anti-HBs) still provide a protective effect at 2-4 years, seven years, and even up to 12 years after primary vaccination. 8,9 Each individual's reaction to the hepatitis B vaccine's protective effect varies, and several factors, including age, male sex, obesity, chronic disease, genetic factors, alcohol use, and immunosuppressive conditions, affect how much seroprotection remains in those who have received the vaccine.…”
Section: Introductionmentioning
confidence: 99%